2014
DOI: 10.1002/adfm.201401760
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Insight into the Structural and Electronic Characteristics of Strontium‐Doped Titanium Dioxide Nanotube Arrays

Abstract: The possibility of in situ doping during electrochemical anodization of titania nanotube arrays is demonstrated and the mechanism and variations in structural and electronic characteristics of the nanotube arrays as after doping is systematically explored. In the presence of strontium as the dopant, bulk analysis shows strontium mainly incorporated into the lattice of TiO2. Surface analysis, however, reveals phase segregation of SrO in the TiO2 matrix at high Sr doping levels. The near edge X‐ray absorption fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…The ionic radius of Sr 2+ (1.18Å) is higher than that of Ti 4+ (0.60Å) and so the insertion of larger ions into the lattice of smaller ions may enhance the possibility of local lattice distortions. 23 The reduction in average crystallite size with increasing concentration of Sr dopant has also been reported by A. Bakhshayesh et al 30 Hamedani et al 29 have reported that Sr 2+ enters the TiO 2 lattice either in the interstitial sites or as a substitution for Ti 4+ . The existence of larger sized Sr 2+ in substitutional sites can cause volume compensating oxygen vacancies; such defect clusters would occur along different [hkl] directions in the TiO 2 lattice resulting in an alteration of the atomic distances 31 and leading to distortion of the structure.…”
Section: Resultssupporting
confidence: 52%
“…The ionic radius of Sr 2+ (1.18Å) is higher than that of Ti 4+ (0.60Å) and so the insertion of larger ions into the lattice of smaller ions may enhance the possibility of local lattice distortions. 23 The reduction in average crystallite size with increasing concentration of Sr dopant has also been reported by A. Bakhshayesh et al 30 Hamedani et al 29 have reported that Sr 2+ enters the TiO 2 lattice either in the interstitial sites or as a substitution for Ti 4+ . The existence of larger sized Sr 2+ in substitutional sites can cause volume compensating oxygen vacancies; such defect clusters would occur along different [hkl] directions in the TiO 2 lattice resulting in an alteration of the atomic distances 31 and leading to distortion of the structure.…”
Section: Resultssupporting
confidence: 52%
“…6,7 In this regard, many studies have been devoted to improve the dynamics including passivation of defects, 8 the use of co-catalysts among others. 9,10 As many studies have shown the dependence of the functionality of the material on its physical dimensions, the best way to improve the transport and collection of charge carriers is to optimize the inherent intrinsic properties of the material. 7,11,12 To this end, controlling the length and the diameter of TiO 2 nanotubes has shown tremendous positive effects on the performance of the materials in solar energy conversion.…”
mentioning
confidence: 99%
“…The distinction could be made only by comparing the intensities of the peaks at 460.5 eV and 461.0 eV. In the case of anatase phase the rst one has higher intensity, [29][30][31] as in the spectrum given in Fig. 4(a).…”
Section: Resultsmentioning
confidence: 99%